Private Sector Consumption Behavior and Non-Keynesian Effects of Fiscal Policy - Bhattacharya, Rina (IMF Working Papers; Working Paper ;, 1999)
This paper explores the hypothesis that the propensity to consume out of income is not constant but varies, perhaps in a nonlinear fashion, with fiscal variables. It examines whether there is any empirical evidence to support the hypothesis that households move from non-Ricardian to Ricardian behavior as government debt reaches high levels and as uncertainty about future taxes increases. The paper also examines the possibility of a relationship (along the lines of the Bertola-Drazen model) between the propensity to consume out of income and the government consumption-to-GDP ratio.